Severe community acquired adenovirus pneumonia in an immunocompetent host successfully treated with IV Cidofovir - Joseph Zhao; Ashton Yap; Eric Wu; Chian Yong Low; Jane Yap (Respiratory Medicine Case Reports, 2020)
Adenovirus is a common cause of acute febrile respiratory infection in children and are generally self-limiting although pneumonia can occur in neonates and adults with compromised immunity. However, severe adenovirus pneumonia in healthy adults has been rarely described. Here, we report a case of severe community-acquired adenovirus pneumonia in a previously healthy patient successfully treated with intravenous Cidofovir.